SOCIO-PHILOSOPHICAL ASPECTS OF THE DEVELOPMENT OF ENTREPRENEURIAL ACTIVITY IN THE PERIOD OF RENEWAL OF OUR COUNTRY - Ganiyev Baxodirjon Sodiqjonovich; Karimov O‘lmasbek Umaraliyevich (Journal Park Publishing, 2023)
The article explores the problem on the basis of scientific-theoretical analysis of the formation and improvement of entrepreneurial skills in the minds of our citizens of modernizing processes carried out in Uzbekistan, as well as the development of a new socio-economic system, socio- philosophical views and defines the tasks arising from recommendations and conclusions.
Keywords: citizens, entrepreneurship, family entrepreneurship, female entrepreneur, social class, philosophical analysis, modernization, transformation.